THE ROLE OF ISLAMIC EDUCATION IN THE RESILIENCE OF FAMILY IN THE ERA OF NEW NORMAL - Munawir Pasaribu (Proceeding International Seminar of Islamic Studies, 2021)
Education is the most important thing achieved by any man, than that any man living will be looking for a place of learning so that he can get a good education. Formal education, informal and non-formal is a great choice in obtaining an education. But now this is due to the presence of pandemic education in the formal that the home is preferred. Problems arise, many in the family feel the confusion to teach the children due to formal education during this open were forced to replace with the education at home with the supervision of parents overall. Parents feel the confusion and even the event of violence at home due to not able to teach their children at home. This paper will be discussed how important the role of parents in shaping the resilience of the family in teaching her children at home. Research using the methodology of the literature by reviewing some of the literature of the Qur'an, the hadith of the Prophet as well as refer to the research-the research that has been fit in the journal. Words Key: Education Of Islam, The Resilience Of Family, The New Normal.